EVALUASI IMPLEMENTASI PERDA NO.6 TAHUN 2021 TENTANG PENYANDANG DISABILITAS DALAM HAK KETENAGAKERJAAN DI KABUPATEN PASURUAN - Lailatul Sakdiyah; A’an Warul Ulum (Journal Publicuho, 2024)
The Pasuruan Regency Government has issued Local Regulation Number 6 of 2021 concerning persons with disabilities, which is basically issued to fulfill the rights of persons with disabilities. The implementation of the regional regulation has not run optimally, especially in the aspect of employment accessibility for persons with disabilities in private companies and regionally-owned companies. This research aims to find out about the evaluation of the policy implementation of Pasuruan Regency regional regulation number 6 of 2021 concerning persons with disabilities in employment rights in Pasuruan Regency. The research method used in this research is a descriptive qualitative method. With data collection techniques, namely observation, interviews , documentation. The results of this study indicate that the implementation of regional regulation number 6 of 2021 concerning persons with disabilities in Pasuruan Regency is still not optimal, the ratio of the number of disabilities to companies receiving disability labor is only around 0.01%. The lack of enforcement of sanctions and the absence of regular supervision of companies, as well as the lack of socialization related to disability rights awareness to companies are obstacle factors.